Peliosis of the spleen: possible association with chronic renal failure and erythropoietin therapy. Issue 838 (August 1995) - Lam, K. Y.; Chan, A. C.; Chan, T. M.
Abstract : Splenic peliosis was identified at necropsy in a 62-year-old woman receiving continuous ambulatory peritoneal dialysis for end-stage renal failure, and erythropoietin therapy for uraemia and anaemia. The immediate cause of death was arrhythmia related to ischaemic heart disease, following an episode of intramuscular haematoma (secondary to platelet dysfunction). The unusual association between peliosis and renal failure, and possibly erythropoietin therapy, is discussed.